Road to Malaysia's Day of Destiny - WELSH, Bridget (Institutional Knowledge at Singapore Management University, 2012)
With well over 100,000 people gathering last week for electoral reform in the largest street protest in the nation's history - and the event marred by violence by both state and non-state actors alike - Malaysian politics has reached an important impasse. The Bersih 3.0 rally and its aftermath reveal that the path ahead for Malaysian politics will grow even more contentious and complex. As the different ‘Bersih stories' pour in, ranging from ‘ordinary' heroism to the darker accounts of beatings and abuse of power, the move of Malaysian politics outside of the realm of elite to the streets and social media is both empowering and scary.